Multidisciplinary Approach for Liver Transplantation in Patients with Nonalcoholic Steatohepatitis: It Takes a Village - Tsai, Eugenia; Patnaik, Ronit; Alkhouri, Naim (Digestive Disease Interventions, 2020)
Nonalcoholic fatty liver disease (NAFLD) is the leading cause of liver disease in Western countries, and its aggressive form, nonalcoholic steatohepatitis (NASH), is a leading cause of cirrhosis and end-stage liver disease. The total number of new liver transplantation waitlist registrants with NASH continues to increase rapidly, making NASH the second most common indication for liver transplantation. Compared with recipients for other etiologies, patients with NASH often have higher rates of obesity, diabetes, dyslipidemia, hypertension, kidney disease, and cardiac disease. Many of these medical comorbidities are independently associated with increased preoperative risk and both short- and long-term complications. The presence of these particular risk factors necessitates the need for early detection, medical optimization, and careful preoperative care. Bariatric surgery is an effective strategy for weight loss and ultimately reducing obesity-related medical complications. In select patients, bariatric surgery—before, during, or after liver transplantation—may be useful to help improve posttransplant outcomes. NAFLD/NASH can present after liver transplantation and occurs as either recurrent or de novo disease. Posttransplant NAFLD occurs in the setting of metabolic syndrome, immunosuppression use, and genetic determinants. Future studies and efforts should focus on optimizing medical management strategies to further improve transplant outcomes in patients with NAFLD.
Keywords: nonalcoholic fatty liver disease; nonalcoholic steatohepatitis; metabolic syndrome; liver transplant; recurrent NAFLD; de novo NAFLD